Analysis of Vibration Characteristic of Laminated Coupling of High Power Permanent Magnet Direct Drive Locomotive - Zhihe Zhang; Shoune Xiao; Guangwu Yang; Youtao Liang; Xiangru Zhang (Jixie chuandong)
In order to study the safe reliability of using the laminated coupling on the permanent magnet direct drive locomotive and the vibration characteristics of laminated coupling under the action of track excitation are analyzed，a small loop test is carried out on a permanent magnet direct-drive locomotive. The real-time monitoring of acceleration of the laminated coupling and its mounting position are obtained. The least square iteration method is used to identify the modal parameters of the laminated coupling at high speed and the modal parameters are obtained. According to the definition of vibration stage drop，the transmission characteristics of transverse，vertical and longitudinal vibration of coupling at high speed are analyzed. Finally，the variation law of acceleration impact range with velocity grade and the variation of acceleration RMS value decay rate with velocity grade are summarized. The analysis of the vibration level drop shows that the three-directional vibration isolation effect of position (c) is better，and the horizontal vibration isolation effect of position (e) is better than the vertical and longitudinal vibrations. By using acceleration impact range and RMS value attenuation rate evaluation also reached the conclusion that position (c) vibration is effectively attenuated. The conclusion provides a reference for the application and optimization design of the laminated coupling in the permanent magnet direct drive locomotive.